Research on axial compression performance test and bearing capacity calculation method of newly assembled hollow lattice wallboard - Liu, Yunlin; Huo, Shangwei; Wu, Zhixin; Yang, Dingguo; Ren, Ke; Liu, Jianhua; Wang, Riguang (Frontiers in Materials, 2024)
With the great development of the construction industry, prefabricated building components have been greatly developed. To study the compressive performance of the new wallboard, the axial compression performance test of six full-scale new lattice wallboards was carried out in this paper. The failure mode, axial pressure-displacement relationship curve, axial compression bearing capacity, and axial pressure-strain relationship of the wallboard were obtained through the experiments. This reveals the influence of the thickness of the concrete surface and the number of ribs on the performance of the wallboard. The test results show that the ultimate bearing capacity of the specimen increases with the increase of the thickness of the concrete surface layer with the same number of ribs. Specimen DW -30 increased by 4% over DW -20 and DW -50 increased by 41.6% over DW -30. The ultimate bearing capacity of the three-ribbed specimens was higher than that of the two-ribbed specimens for the same concrete face thickness, about 1.11 times that of the two-ribbed specimens. The concrete facing thickness and the number of ribs have a restraining effect on the deformation of the wallboard. Additionally, the calculation formula of axial bearing capacity of type latticed wallboard considering the influence of eccentric compression was proposed, which can provide a reference for engineering calculation.